Electrochemical detection of Zn(II) using an electrode modified with calixarene - Roslan, Nur Izzah (2016)
This work demonstrates a simple approach of developing electrochemical heavy metal ions sensor by employing calix[4]arene on indium tin oxide (ITO) electrode. The method involves the formation of self-assembled monolayers (SAMs) of 3-aminotrimethoxysilane (APTMS) on ITO, acting as a template for calix[4]arene attachment in which the different formation time of APTMS was initially studied. Contact angle and atomic force microscopy (AFM) characterizations were performed to study the surface wettability, roughness and topography. With the increasing immersion time, the values of contact angle and roughness increased. The values continue to increase after modifying the surface with calixarene. The surface modification with APTMS and calix[4]arene was confirmed using X-ray photoelectron spectroscopy (XPS) by analyzing the nitrogen and carbon regions. Cyclic voltammetry was used to monitor the blocking properties of films formed on ITO. It showed that the blocking properties modified with APTMS were improved by the modification of calix[4]arene on amine terminated ITO surfaces. Subsequent step was, the introduction of common heavy metal ions (Zn(II), Cu(II), and Fe(II)) towards the modify electrode. The electrochemical study was done by using differential pulse voltammetry (DPV) analysis by comparing the current produced for concentration of Zn(II), Cu(II) and Fe(II); the linear range of 1 x 10-2 M to 1 x 10-10 M, detection limit of 1.51 x 10-13 M for Zn(II); while with the linear range of 6 x 10-5 M to 2 x 10-6 M, detection limit of 1.31 x 10-7 M for Cu(II); and with the linear range of 1 x 10-2 M to1 x 10-7 M, detection limit of 2.06 x 10-8 M for Fe(II). The effect of simultaneous ions was studied by comparing which ion interfere the most at the same concentration of analytes. The interference study also was done by using interfere ions such as Cu(II), Fe(II), Pb(II), Cd(II), and Ni(II) towards up to 1000-fold concentration of Zn(II). The sensitive and selective determination of Zn(II) make calix[4]arene a promising candidate for practical application in the field of detecting heavy metal ions.